VALORIZATION OF PAPAYA PEEL WASTE: DEVELOPMENT AND QUALITY CHARACTERIZATION OF FORTIFIED COOKIES AND YOGURT - Pooja Bhatt; Anishka Singh; Chef Shweta; Jyoti Bohra Mahar (The Bioscan, 2025)
This study focuses on the formulationof cookies and yoghurt incorporating papaya peel powder (PPP) as a functional ingredient and its quality evaluation. Papaya peel is very beneficial byproduct, it isrich indietary fiber, antioxidants, and bioactive compounds. The papaya peel was processed into powder and is incorporated in different amounts, in order to increase the nutritional profile and the functional properties of the products. The cookies were formulated by incorporating the papaya peel powder at three different levels: 2%, 4% and 10% (PPC1, PPC2, PPC3, respectively) and yoghurt was also enriched with PPP at three different levels: 1%, 2%, 3% (PPY1, PPY2, PPY3, respectively). The papaya peel powder was evaluated to analyze the proximate composition andnutritional properties. The incorporation of PPP imparted distinct color and flavor characteristics, which influenced consumer acceptability. The sensory evaluation revealed that PPC2 has the highest overall acceptability 7.06± 0.64, with 7.2± 1.31 for color, 7.2± 1.54 for appearance, 6.5± 1.17 for texture and 7± 1.63 for taste.In the case of yoghurt, PPY1 has shown the highest overall acceptability 7.76± 0.56, with 8.2± 0.91 for color, 8± 0.47 for appearance,7.5± 0.52 for aroma and 7.4± 0.69 for taste.